Sistem Antrian Untuk Mempermudah Pelayanan Pasien Rawat Jalan Pada Puskesmas XYZ - Lumba, Ester (LPPM of STIMIK ESQ, 2015)
Puskesmas is a functional organization for providing health service which is comprehensive, integrates, equal, reachable and cost friendly for the people. Puskemas emphasizes its service on the optimum level of health to the wider society. To enhance the quality of the services to the public, it is time for a clinic to be supported by a computer application that can help the patients who have to wait with a long queue when they want to get the services from it. Queuing application with web-based system can help the patients by online registration and get the queuing number without come to the clinic before their visit. By this system, the patients can also observe the progress of the queue from the website, take their time to wait in the outside of the clinic and arrange their coming without stay for a longer time before their turn. The clinic itself may apply First Come First Served (FCFS) queuing system which means a patient will get handled until the previous patient is finished. Furthermore, this application will help the clinic officer to manage the existing data in it without keep calling the patients one by one manually. Subsequently, the operator will only press the button in the queuing application to call the next patient